"The body of Christ has AIDS" A study on the notion of the body of Christ in African theologies responding to HIV and AIDS - Klinken, Adriaan S. Van (Missionalia : Southern African Journal of Mission Studies, 2008)
In the responses of African theologians to the challenges raised by HIV and AIDS, they often refer to the metaphor of the body of Christ. This article investigates how this metaphor is used and understood by African theologians and why it has become so prominent in their reflections on the reality of HIV and AIDS. Two dimensions of the metaphor are highlighted: an ecclesiological one, concerning the Church and its mission in the context of HIV and AIDS, and a sacramental one, concerning the significance of the Eucharist/Holy Communion in the HIV and AIDS context. It is argued that the particular attraction of the metaphor is in its notion of solidarity. For this reason "the body of Christ" has become a central biblical metaphor in what can be called an HIV and AIDS liberation theology. Furthermore, it is argued that the use of the metaphor of the body of Christ in African theologies responding to HIV and AIDS has a theological impact that transcends the African context. This raises critical questions for Christian Churches and for theology worldwide.
Free